2012
DOI: 10.1177/1091581812463254
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Like Disruptive Effects of Dietary Exposure to Bisphenol A or 17α-Ethinyl Estradiol in CD1 Mice

Abstract: Bisphenol A (BPA) is an endocrine disrupting chemical that is ubiquitous in wild and built environments. Due to variability in study design, the disruptive effects of BPA have proven difficult to experimentally replicate. This study was designed to assess the disruptive actions of dietary BPA exposure, while carefully controlling for known confounders. Parental CD1 mice were acclimated to defined diet containing BPA (0.03, 0.3, 3, 30, or 300 ppm) or 17α-ethinyl estradiol (EE; 0.0001, 0.001, and 0.01 ppm) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 47 publications
(82 reference statements)
9
59
0
Order By: Relevance
“…Similarly, others have used soy-free diets in multigenerational reproductive studies in rats and mice ( e.g. , Kendig et al, 2012; Sprando et al, 2000); however, some literature suggested that the specific soy- and alfalfa-free diet that we had used might be problematic in studies in the CD-1 mouse (Ruhlen et al, 2008). This diet, designated 5K96, was originally designed to be nutritionally equivalent to the open-formula NIH-31 diet.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, others have used soy-free diets in multigenerational reproductive studies in rats and mice ( e.g. , Kendig et al, 2012; Sprando et al, 2000); however, some literature suggested that the specific soy- and alfalfa-free diet that we had used might be problematic in studies in the CD-1 mouse (Ruhlen et al, 2008). This diet, designated 5K96, was originally designed to be nutritionally equivalent to the open-formula NIH-31 diet.…”
Section: Introductionmentioning
confidence: 99%
“…However, these results may not be reliable, as estrus cycling is not yet consistent in mice at this age, and given the small number of individual mice studied (n=5 per group). This study, and three others [6971], examine effects of BPA on uterine weights. Unfortunately, none of these studies [61,6771] reported measures to control for effects of the estrus cycle on uterine weights, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This study, and three others [6971], examine effects of BPA on uterine weights. Unfortunately, none of these studies [61,6771] reported measures to control for effects of the estrus cycle on uterine weights, i.e. by collecting uteri at a consistent stage of the estrus cycle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations